A detective of intramural ectopic pregnancy: The use of pituitrin under hysteroscopy combined with laparoscopy. Issue 12 (24th March 2023) - Guo, Yanchao; Feng, Tongfu; Du, Xin
Abstract : Rationale: Intramural pregnancy is a rare ectopic pregnancy in which the gestational sac is implanted between the muscle walls. Due to the lack of specific clinical manifestations, it is easy to misdiagnose or miss them. If it is allowed to get worse, the uterus will burst, and there will be a lot of bleeding in the later stages, which could lead to the death of the patient. Patient concerns: The patient had no history of uterine surgery, embryo transplantation, or any other operations. She complained of having abdominal distention and swelling of the waist but no vaginal bleeding or lower abdomen discomfort. Diagnoses: According to her transvaginal ultrasonography, we highly suspected ectopic pregnancy. Hysteroscopy combined with laparoscopy is an effective treatment option that can prevent life-threatening problems. During the surgery, pituitrin helped find the gestational sac, and the pathology report confirmed that it was an intramural pregnancy. Interventions: Hysteroscopy combined with laparoscopy is an effective treatment option that can prevent life-threatening problems. During the surgery, we used pituitrin to help find the gestational sac. The use of pituitrin can minimize bleeding during a uterine operation and indicate the location of an intramural pregnancy, helping surgeons to complete the operation successfully. Outcomes: The patient recovered quickly and was discharged on the 4th day after surgery, with a significant decrease in human chorionic gonadotrophin (HCG) levels from 14, 792.26 mIU/mL before surgery to 1071.40 mIU/mL at discharge. During the follow up, her HCG level dropped to 50.90 mIU/mL on the 14th day after the surgery. She monitored the HCG levels intermittently until they fell within the normal range. Lessons: Intramural pregnancy is a rare form of ectopic pregnancy, and it is difficult to diagnose early on. This may result in uterine rupture or even life-threatening hemorrhage. If an intramural pregnancy is suspected in early pregnancy, hysteroscopy combined with laparoscopy is advised, and if necessary, low-dose posterior pituitary hormone can enhance uterine contractions and better reveal the position of the gestational sac within the uterine wall.